Long-term Efficacy and Safety of Everolimus Versus Mycophenolate in Kidney Transplant Recipients Receiving Tacrolimus. Issue 2 (February 2022) - Nunes Ficher, Klaus; Dreige, Yasmin; Gessolo Lins, Paulo Ricardo; Nicolau Ferreira, Alexandra; Toniato de Rezende Freschi, Juliana; Linhares, Kamilla; Stopa Martins, Suelen; Custodio, Luciana; Cristelli, Marina; Viana, Laila; Wagner Santos, Daniel; de Marco, Renato; et al.
Abstract : Background: The short-term efficacy and safety of everolimus in combination with tacrolimus have been described in several clinical trials. Yet, detailed long-term data comparing the use of everolimus or mycophenolate in kidney transplant recipients receiving tacrolimus are lacking. Methods: This is a 5-y follow-up post hoc analysis of a prospective trial including 288 patients who were randomized to receive a single 3-mg/kg dose of rabbit antithymocyte globulin, tacrolimus, everolimus (EVR), and prednisone (rabbit antithymocyte globulin/EVR, n = 85); basiliximab, tacrolimus, everolimus, and prednisone (basiliximab/EVR, n = 102); or basiliximab, tacrolimus, mycophenolate, and prednisone (basiliximab/mycophenolate, n = 101). Results: There were no differences in the incidence of treatment failure (31.8% versus 40.2% versus 34.7%, P  = 0.468), de novo donor-specific HLA antibodies (6.5% versus 11.7% versus 4.0%, P  = 0.185), patient (92.9% versus 94.1% versus 92.1%, P  = 0.854), and death-censored graft (87.1% versus 90.2% versus 85.1%, P  = 0.498) survivals. Using a sensitive analysis, the trajectories of estimated glomerular filtration rate were comparable in the intention-to-treat ( P  = 0.145) and per protocol ( P  = 0.354) populations. There were no differences in study drug discontinuation rate (22.4% versus 30.4% versus 17.8%, P  = 0.103). Conclusions: In summary, this analysis in a cohort of de novo low/moderate immunologic risk kidney transplant recipients suggests that the use of a single 3 mg/kg rabbit antithymocyte globulin dose followed by EVR combined with reduced tacrolimus concentrations was associated with similar efficacy and renal function compared with the standard of care immunosuppressive regimen. Abstract : Supplemental Digital Content is available in the text.